Ten Principles to Guide the Public Financing of Higher Education - Hauptman, Arthur M. (International Higher Education, 2012)
Based on two decades of experience in dealing with more than two dozen countries, the author lays out ten principles that should help in strengthening higher education financing structures. These principles include defining the role of politicians and other officials in appropriating funds for higher education and in deciding on how they are allocated, and the importance of linking the key policies of funding institutions, setting fees and providing student financial support. The article also recognizes the importance of having a strong quality assurance system to ensure financing policies are effective in meeting national goals.